Chemotherapy in "oat cell" carcinoma of the lung: PRELIMINARY RESULTS OF TREATMENT WITH A POLYCHEMOTHERAPY SCHEME OF CYTOKINETIC BASES - Carámbula, José A.; Fernández, Alvear; Varela, Juan; Martínez, Lem (Cirugía del Uruguay, 1982)
A preliminary evaluation of the therapeutical results and the tolerance achieved in eight patients with "oat cell" carcinoma of the lung treated with a intennitent scheme of chemoimm consisting of five drugs -CFM, MTX, ADR, CCNU and Parvum: "EMACC"-, is reported. Under this treatment it was obtained a tumoral remission rate of 5/8 (62.5 %) ; in seven patients it was found an improvement in the perfo-anance status (87.5%), and after seven months of follow-up, 61.5% of the patients are alive, with an acceptable clinical tolerance but a high toxic haematologic cost. Different considerations about the biological behaviour of the disease and the rational way to focus its treatment are made, the cytocinetic basis on the design of the reported scheme are established and it is remarked the non merggence of encephalic metastases through the treatment time. This last fact is related to the chemoprophylactic effect of CCNU on the C.N.S.